Ex vivo flow mammalian cell electropulsation - Vernhes, Marie Christine (Radiology and oncology (Ljubljana), 2004)
Cell electropulsation brings a local and reversible permeabilization of cell membranes. This gives the technical possibility to introduce (load) exogenous compounds (drugs, proteins, DNA) into cells. Flow-through electropulsation allows to treat a large volume (number) of cells as requested for cell therapy. Cells are flowing through a pulsing chamber where they are submitted to a well-defined number of calibrated pulses. A proper setting of pulse frequency and flow rate controls the number of pulses. A large volume of cellscan therefore be electrotreated in a small sized pulsing chamber. The viability of pulsed cells appears to be greatly preserved.
Keywords: celična membrana; Celična membrana, propustnost; Cell Membrane Permeability; CHO celice; Cho Cells; citologija; Electroporation; Elektroporacija; permeabilnost celične membrane